2017
DOI: 10.1063/1.4993144
|View full text |Cite
|
Sign up to set email alerts
|

Vortex scaling ranges in two-dimensional turbulence

Abstract: 1We survey the role of coherent vortices in two-dimensional turbulence, including formation mechanisms, implications for classical similarity and inertial range theories, and characteristics of the vortex populations. We review early work on the spatial and temporal scaling properties of vortices in freely evolving turbulence, and more recent developments, including a spatiotemporal scaling theory for vortices in the forced inverse energy cascade. We emphasize that Kraichnan-Batchelor similarity theories and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The numerous merger we studied, together with previous studies [6][7][8][9][10][11] , suggests that the merger of large mesoscale eddies are key for the transfer of heat and energy to large scales, through the mixing of water masses in surface and sub-surface. Recent studies suggested that, in the ocean, the number of vortex splitting is comparable to that of the vortex merger 30 .…”
Section: Discussionmentioning
confidence: 53%
“…The numerous merger we studied, together with previous studies [6][7][8][9][10][11] , suggests that the merger of large mesoscale eddies are key for the transfer of heat and energy to large scales, through the mixing of water masses in surface and sub-surface. Recent studies suggested that, in the ocean, the number of vortex splitting is comparable to that of the vortex merger 30 .…”
Section: Discussionmentioning
confidence: 53%
“…However, Benzi et al (1988) suggest that the vortex population statistics obey a self-similar scaling that resembles the KBL scaling of the inertial ranges. This self-similarity, which is supported by the work of Burgess et al (2017), encourages the hope that the coherent vortices might yet fit within the standard model of two-dimensional turbulence. For a recent review of two-dimensional turbulence see Boffetta & Ecke (2012).…”
Section: Introductionmentioning
confidence: 58%
“…Using barotropic (2D) models is a common first step to evaluate coherent eddies in large-scale flows [52]. Inviscid decay (Landau damping) of asymmetric perturbations to stable vortices is responsible for the process of vortex axisymmetrication [53] and the energy transfer from a weak satellite at the periphery of a strong vortex due to curved stretching out [54].…”
Section: Discussionmentioning
confidence: 99%